Unmasking the Impact of Bureaucratic Violence - Gren, Nina; Abdelhady, Dalia; Joormann, Martin (Refuge: Canada’s Journal on Refugees, 2024)
This introductory article introduces the concept of bureaucratic violence as a partly new way of understanding and analyzing refugees’ encounters with bureaucratic structures within authorities and organizations. Violence or the threat of violence is an inevitable part of the experiences of most forcibly displaced people. In this Special Issue, we highlight how bureaucracies as social institutions, besides providing access to rights, also impact refugees in ways that are constraining, humiliating, soul-killing and, sometimes, life-threatening. We present the theoretical underpinnings of the term bureaucratic violence and, thus, the conceptual framework that connects the different case studies included.